Parabolic curves in ℂ3 - Marco Abate; Francesca Tovena (Abstract and Applied Analysis)
We discuss a family of holomorphic self-maps of ℂ3 tangent to the identity at the origin presenting dynamical phenomena not appearing for lower-dimensional maps.